FORMATION OF READY TEACHER’S READYNESS TO CREATIVE ACTIVITY BY MEANS MODULAR-BLOCK LEARNING - Ivanova, V.V. (Pedagogy of Higher and Secondary Education, 2007)
At this article is considered possibi lities of modulus-hlocks structured of educational information at the forming of readiness the future teacher to the creative professional activity.